Caracterização da resposta imune induzida pelo vírus Vaccinia Ankara modificado (MVA) em modelo murino - Lorena Falabella Daher de Freitas (2011)
Since 1796, when the British physician Edward Jenner introduced the concept of vaccination, it became the most important intervention strategy developed to prevent the onset of infectious diseases. Nevertheless, none of the existing vaccines has managed to present all advantages that make an ideal vaccine. In this context, recombinant viral vectors appear as a promising tool for the development of new vaccines as well as for the improvement of the existing ones. The Modified Vaccinia virus Ankara (MVA), a member of the Poxviridae family, was generated after more 570 passages in chicken embryo fibroblasts. After that, a virus highly attenuated and unable to replicate in mammalian cells was obtained, due to the lost of approximately 15% of its parental genome. The loss included genes related to host immune regulation, immune evasion and host range. Thus, the MVA is considered a safe vaccine vector, and has been used in our lab in attempts to generate new vaccines. Recentstudies from our group have shown that natural infections caused Vaccinia virus (VACV) strains circulating in Brazil induced a down-modulation of the host immune system. Due to the genetic similarity between MVA and the virulent VACV isolates, we decided toinvestigate whether MVA could induce a similar response pattern, which is not desirable in a good vaccine vector. Therefore, the aim of this work was to study the immune response generated after the MVA infection in mice, comparing it with infections caused by two other VACV strains: the Lister (LST) replicative vaccine strain and the virulent Western Reserve(WR) strain. In order to reach those aims, 4 groups composed of 7 BALB/c mice, 6 to 7 weeks old, were intranasally infected with MVA, LST or WR strains. A control group was inoculated with PBS. After 7 or 14 days, their spleens were collected in order to evaluate cell proliferation, cell activation profile intracytoplasmatic cytokine production. Results showed a down modulation in the cell activation profile and in the cytokine production in spleen cells from animals infected with WR. On the other hand, cells from the MVA-infected animals presented a profile similar to that of the control group. These results may be attributed to theloss of immune regulation genes during the MVA attenuation process, and are desirable characteristics in a good vaccine viral vector.